Determinación de la calidad del agua por medio de bioindicadores (macroinvertebrados) en el Río Cunuyacu provincia de Cotopaxi, período 2020-2021. - Jiménez Arias, José Santiago (2021)
The following research work was carried out in the Cunuyacu river belonging to the province of Cotopaxi - Ecuador. Previously, georeferencing points were delimited in the river area with the objective of knowing its environmental quality through biological indexes (BMWP/col, ABI, E.P.T, Shannon - Weaver) and the water quality index (ICA NSF). Three sampling points were planned along the river bed, in places of lower to higher volume of wastewater discharges, located from the source of the river to its mouth because in P3: Molinos Poultier during the month of January there was abundant rainfall, this could be a factor for the abundance of macroinvertebrates was usual for each site and for each time of the year, for this reason a relationship between water growth was evidenced. Three methodologies were used, the first was qualitative, in which the macroinvertebrates were identified and placed according to their taxonomic levels of class, order and family. The second method was quantitative, which consisted of counting macroinvertebrates that were collected at three different sampling points located at the beginning, middle and end of the Cunuyacu River. The third method is the inductive method that was used to establish the level of contamination of the Cunuyacu River; water samples were collected and sent to the laboratory for analysis. To analyze the main parameters, which were compared with current regulations TULSMA, BOOK VI; APPENDIX I, Table 3, Admissible quality criteria for agricultural water. The indices (BMWP/col, ABI, E.P.T, Shannon - Weaver) were used to determine the water quality of the Cunuyacu River with the collection and identification of macroinvertebrates. The BMWP/col index gave us the result that the water quality is Critical, while the ABI and E.P.T indexes are found in Bad water quality, therefore the Shannon - Weaver index with a high biodiversity of 6.96. Regarding the water quality index (ICA NSF), the parameters analyzed in November and December in the Cunuyacu River at the three sampling points showed that the pH parameters had a result of (8.10), while the Total Solids (499.66 mg/L) and Fecal Coliforms (183 NMP/100mL) of the Cunuyacu water body are within the permissible limits. According to the Environmental Quality and Effluent Discharge Standard (water resource) in Book VI, Annex 1, Table 3, Admissible quality criteria for agricultural water. For Ecuador, the regulation establishes that water for agricultural use should be a maximum of 1000 NMP/100 mL (Most Probable Number per 100 milliliters of water) in Fecal Coliforms), and an optimal pH range of 6.5 -9 of Total Solids in a range of 3000.0 mg/L.